Designer microbiomes for environmental, energy and health biotechnology. (June 2018) - Strous, Marc; Sharp, Christine
Abstract : Biotechnology conventionally uses pure strains of microorganisms to realize a desired conversion. The design of functional microbiomes is becoming a powerful alternative for when an aseptic environment is not an option, either for economic reasons or if the environment is intrinsically open. Rapid technological developments in combined -omics approaches is enabling the engineering and optimization of highly complex microbiomes. This review outlines emerging principles of design and provides examples of successful approaches and interventions in wastewater treatment, bioenergy production and the human intestinal microbiome.